2016
DOI: 10.1097/prs.0000000000002702
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Telemedicine in Wound Care: A Review and Analysis of a Database of 5,795 Patients from a Mobile Wound-Healing Center in Languedoc-Roussillon, France

Abstract: There is an increasing demand for assistance from professionals not specialized in wound healing, facing complex wounds. The goal is to enable the spread of expertise beyond major medical centers. Several limitations and barriers to the application of telemedicine in all settings are evident, including over diagnosis, dependence on a functional telecommunication system, and various legal aspects. The CICAT network in France provides an example of a how telemedicine may be of benefit in wound care, although it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…The authors found that patients in the TM and control groups had similar healing time (43 vs 45 days; P =.83) as well as similar ulcer healing rate (odds ratio 0.86, 95% CI 0.57-1.33; P =.53). A 10-year study of 5795 patients in France also provided an example of how TM might be of benefit in wound care [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that patients in the TM and control groups had similar healing time (43 vs 45 days; P =.83) as well as similar ulcer healing rate (odds ratio 0.86, 95% CI 0.57-1.33; P =.53). A 10-year study of 5795 patients in France also provided an example of how TM might be of benefit in wound care [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has also been shown to be a useful communication tool in a home care setting. 16 27 The modern technique of video communication through iPad or smartphone is easy to use, and is now widely available in both rural and urban societies.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Another example is a telemedicine wound care model, which has produced reductions in both hospital admissions and patient transportations. 16 The use of three-dimensional images has shown high concordance with inperson consultation for assessment and measurement of wounds. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Other experiments in telemedicine in the field of chronic wounds exist in France such as CICAT in Languedoc-Roussillon (now Occitanie) and TELAP in Normandy. Thus, the service of telemedicine Domoplaies has allowed a rate of healing of complex wounds and/or chronic conditions at half the cost if compared to typical treatment according to a medico-economic analysis by the CICAT-Occitanie network [27]. …”
Section: Methodsmentioning
confidence: 99%